Somatic Development of Primary School Children - Normurodovna, Hazratova Нulkar; Keldiyorovna, Meyliyeva Ozada (American Journal of Bioscience and Clinical Integrity, 2026)
The article presents the results of a study on the indicators of physical development of rural schoolchildren aged 7–10 years. The obtained data indicate that the body weight, height, and chest circumference of students increase with age. In particular, among children aged 7–8 years, the above-mentioned indicators do not significantly deviate from the norm. Among boys and especially girls aged 9–10 years, the indicators of height, chest circumference, and Quetelet index exceed the standard values. The study of students’ physical development is one of the important steps toward further strengthening their health.